Development of a continuous-flow tubular reactor for synthesis of 5-hydroxymethylfurfural from fructose using heterogeneous solid acid catalysts in biphasic reaction medium. (26th April 2021) - Souzanchi, Sadra; Nazari, Laleh; Rao, Kasanneni Tirumala Venkateswara; Yuan, Zhongshun; Tan, Zhongchao; Xu, Chunbao Charles
Abstract : 5-Hydroxymethylfurfural (5-HMF) is an important biomass-derived platform chemical used to produce polymers, biofuels, and other valuable industrial chemicals. Abstract : 5-Hydroxymethylfurfural (5-HMF) is an important biomass-derived platform chemical used to produce polymers, biofuels, and other valuable industrial chemicals. In this work, 5-HMF was synthesized from biomass-derived fructose through a continuous flow process using heterogeneous solid acid catalysts. Different solid acid catalysts, including niobium-based catalysts, Amberlyst 15, and Amberlyst 36, were tested for selective dehydration of fructose to 5-HMF in a biphasic (H2 O/MIBK) continuous-flow tubular reactor. The catalysts were characterized using complementary techniques, including BET surface area, XRD, TGA, NH3 -TPD, FT-IR, and pyridine-FT-IR. We also studied the effects of different reaction parameters such as the initial fructose concentration, reaction temperature, feeding flow rate, and aqueous-to-organic phase ratio. The optimal conditions were determined to be 150 °C temperature, a 0.25 ml min −1 feeding flow rate, 200 mg ml −1 NaCl concentration, 200 and 400 mg ml −1 fructose concentrations, and aqueous-to-organic phase ratios of 1 : 5 and 1 : 10. In addition, niobium phosphate (NbP), synthetic sulphated niobia (NbS) and Amberlyst 36 (Amb. 36) were active and selective, leading to 5-HMF yields in the range of 54–60% under the optimal operating conditions. Meanwhile, the Amb. 36 catalyst exhibited a 5-HMF selectivity of 70% at 150 °C, and therefore it was selected as the catalyst for the fructose dehydration reaction. Additionally, the Amb. 36 catalyst showed consistent catalytic activity and selectivity during a time-on-stream of 8 h. Furthermore, a reusability test with the used catalyst demonstrated that this catalyst can be recycled and reused without losing its catalytic activity.